Tracked Changes. Connectors for electrical and electronic equipment. Product requirements. Detail specification for 8-way, shielded, free and fixed connectors for I/O and data transmission with frequencies up to 500 MHz and current-carrying capacity in industrial environments Part 3-122, (23rd March 2022) - British Standards Institution,
No abstract available